2011
DOI: 10.1159/000324500
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery Influences the Regression of Abnormal Cervical Cytology

Abstract: Aims: The purpose was to investigate the influence of delivery mode on the postpartum regression of abnormal cervical cytology. Methods: A retrospective review was conducted of 64 pregnant women with abnormal cervical cytology at Yonsei University Health System in Korea between 2001 and 2008. A Papanicolaou smear and pathological data were categorized into three groups by cervical intraepithelial neoplasia classification. Postpartum evaluation was taken 3–6 months after delivery. The regression rates of cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
8
1
1
Order By: Relevance
“…This result correlates with findings of other previously conducted studies (11,(16)(17)(18)(19). However, this is in contrast with the results of five other studies (10,13,(20)(21)(22) which showed higher regression rates in women who delivered vaginally.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result correlates with findings of other previously conducted studies (11,(16)(17)(18)(19). However, this is in contrast with the results of five other studies (10,13,(20)(21)(22) which showed higher regression rates in women who delivered vaginally.…”
Section: Discussionsupporting
confidence: 88%
“…The overall regression rates (cytological regression: 40%, histological regression: 30%) in our study population are similar to those reported in previous studies (3,15,23,24). Chung et al reported a total regression rate of 92.9% which is much higher than the one found in our study (10). The small population of both studies is taken into account for such different findings.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…6 Prior studies suggest a role for inflammation in the spontaneous regression of HPV-related cytologic changes. [7][8][9] All IUDs are associated with some level of local cellular and humoral inflammatory reaction of the endometrium. Copper-containing IUDs (Paragard) release ions that increase prostaglandin levels and white blood cells within the uterine and tubal fluids causing chronic inflammation and a spermicidal effect.…”
Section: Level Of Evidence: IImentioning
confidence: 99%
“…Einige Studien berichten über höhere Remissionsraten bei Spontangeburt im Vergleich zur Sectio caesarea (67 vs. 12%; [19,20]), in anderen konnte kein signifikanter Unterschied festgestellt werden [17,18]. …”
Section: Cin 3 In Der Schwangerschaftunclassified